CCR5 deficiency in aged mice causes a decrease in bone mass - Oh, Eun-Ji; Zang, Yaran; Kim, Jung-Woo; Lee, Mi Nam; Song, Ju Han; Oh, Sin-Hye; Kwon, Seung Hee; Yang, Jin-Woo; Koh, Jeong-Tae (International journal of oral biology, 2019)
The CC chemokine receptor 5 (CCR5) is a G protein-coupled receptor that regulates chemotaxis and effector functions of immune cells. It also serves as the major co-receptor for the entry of human immunodeficiency virus (HIV). Recently, CCR5 inhibitors have been developed and used for the treatment or prevention of HIV infections. Additionally, it has been identified that CCR5 controls bone homeostasis by regulating osteoclastogenesis and the communication between osteoblasts and osteoclasts. However, the effects of CCR5 inhibition on bone tissue in elderly patients are unknown. This study aimed to examine the bone phenotype of aged CCR5 knockout (KO) mice. Femoral and tibial bones were isolated from 12-month and 18-month old wild-type (WT) and CCR5 KO mice, and microcomputed tomography and histology analyses were performed. Twelve-month-old CCR5 KO mice exhibited a decreased trabecular bone mass and cortical bone thickness in both femoral and tibial bones compared with agematched WT mice. Eighteen-month-old mice also showed a decreased trabecular bone mass in femurs compared with control WT mice, but not in tibial bones. Unlike in 12-month-old mice, the cortical margin of femurs and tibias in 18-month-old mice were rough, likely because they were aggravated by the deficiency of CCR5. Overall, our data suggest that the deficiency of CCR5 with aging can cause severe bone loss. When CCR5 inhibitors or CCR5 inactivating technologies are used in elderly patients, a preventive strategy for bone loss should be considered.